2020
DOI: 10.3389/fcvm.2020.599807
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Pharmacists' Assistance for Patients With Established Cardiovascular Diseases During the COVID-19 Pandemic: Insights From Southern India

Abstract: Objectives: We aimed to assess the clinical pharmacist-initiated telephone-based patient education and self-management support for patients with cardiovascular disease during the nationwide lockdown during COVID-19 pandemic.Methods: A prospective single-center telephone-based cross-sectional study was conducted among patients at the Cardiology Department and its speciality clinic at a 1,800-bed tertiary care hospital in Southern India. A validated 8-item clinical pharmacist aided on-call questionnaire with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…After removing duplicates (n=795), and screening by the title and abstract (n=230) and full text (n=121), 43 articles were included in this review 20–62. Among the included studies were 25 observational studies (including 13 cross-sectional studies,36–39 43–48 54 59 60 5 case series,34 35 49–51 5 retrospective study,40 41 52 53 55 1 prospective study61 and 1 interview study42 and 18 descriptive studies 20–33 56–58 62. The general characteristics of the included studies are summarised in online supplemental table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After removing duplicates (n=795), and screening by the title and abstract (n=230) and full text (n=121), 43 articles were included in this review 20–62. Among the included studies were 25 observational studies (including 13 cross-sectional studies,36–39 43–48 54 59 60 5 case series,34 35 49–51 5 retrospective study,40 41 52 53 55 1 prospective study61 and 1 interview study42 and 18 descriptive studies 20–33 56–58 62. The general characteristics of the included studies are summarised in online supplemental table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the included studies are summarised in online supplemental table 1. The majority of the studies reported about the use of eHealth by hospital pharmacists,20 21 23 25 29–31 33–35 37–41 43 46–49 52–55 58 59 61 followed by community pharmacists 28 35 45 46 50 51 54 60 62. Patients with chronic diseases27 31 32 34 37 39 40 43 44 48 52 54 57 60–62 were the primary targets populations of PC-eHealth interventions, followed by patients with COVID-1926 34 42 46 49–51 58 and patients with cancer 27 31 37 40…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations